2014
DOI: 10.1259/bjr.20130613
|View full text |Cite
|
Sign up to set email alerts
|

Using “iDose4” iterative reconstruction algorithm in adults' chest–abdomen–pelvis CT examinations: effect on image quality in relation to patient radiation exposure

Abstract: Our results suggest that the iterative acquisition protocol provides great potential for reducing radiation exposure and maintaining or improving image quality in CAP CT examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 18 publications
(29 reference statements)
1
32
0
Order By: Relevance
“…However, recent technologic advances of CT include iterative reconstruction technique, which prevents the photon starvation artifact and additional streak artifact before image creation with reduction of radiation dose [15,16]. A hybrid iterative reconstruction technique called iDose4 (Philips Healthcare) has been developed that can provide substantial improvement of image quality with reduced radiation dose [17,18]. We have recently accumulated experience with chest CT examinations using iDose4, and, empirically, we could deduce that high-density esophageal FB would be well detected on submillisievert CT examination with iDose4.…”
Section: Gastrointestinal Imaging Original Researchmentioning
confidence: 99%
“…However, recent technologic advances of CT include iterative reconstruction technique, which prevents the photon starvation artifact and additional streak artifact before image creation with reduction of radiation dose [15,16]. A hybrid iterative reconstruction technique called iDose4 (Philips Healthcare) has been developed that can provide substantial improvement of image quality with reduced radiation dose [17,18]. We have recently accumulated experience with chest CT examinations using iDose4, and, empirically, we could deduce that high-density esophageal FB would be well detected on submillisievert CT examination with iDose4.…”
Section: Gastrointestinal Imaging Original Researchmentioning
confidence: 99%
“…This result is similar as the literatures. [11][12][13][14] Although the HU was increased in the high density material like bone, the dose change in the plans for the spine target was less than 0.5%. For the lung plans considering the low density around the target (known as a heterogeneity), the change due to the iDose was less than 1.1%.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] As one of them, Philips provides a 4th gene ration iterative reconstruction algorithm, iDose (Philips Medical Systems, Cleveland, OH, USA). [11][12][13] Although the image contrast increment by using the retrospective reconstruction algorithm is beneficial for a diagnostic CT, the verification of the HU changes is required to use for the dose calculation in treatment planning using the correlation table of HU to material density.…”
Section: -7)mentioning
confidence: 99%
“…While the study on CT perfusion scans of the pancreas reported no notable dif-ferences in subjective image quality and mean CNR values between reduced-dose (10.81 mSv) iDose 4 images and standarddose (23.37 mSv) FBP images, improvements in both objective and subjective image quality in iDose 4 images were noted in another study performed in chest-abdomen-pelvis CT scans, with an effective dose reduction of 46.5% (7.1 mSv versus 12.9 mSv). 49,52 Interestingly, reduced-dose iDose 4 images were given poorer subjective image quality scores by radiologists when compared to standard-dose FBP images in the study involving low-dose CT scans of the brain, despite lower objective noise levels in the iDose 4 images.…”
Section: Performance Of the Idose 4 Algorithmmentioning
confidence: 97%